2015
DOI: 10.1007/s13594-015-0273-y
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal diversity and safety evaluation of enterococci population from goat milk in a farm

Abstract: The presence and genetic diversity of enterococci in raw goat milk sampled in a farm during consecutive seasons were evaluated. Representative strains were screened for virulence determinants, susceptibility to antibiotics and the presence of genes involved in biogenic amine production. Counts of enterococci ranged between 2.80×10 1 and 2.50×10 3 cfu.mL -1 with summer samples showing the highest counts and winter samples the lowest. A total of 695 enterococci were isolated and genotyped. One hundred and thirty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 35 publications
1
8
1
1
Order By: Relevance
“…All the five strains showed the expected amplicon of 1100 bp corresponding to the tdc gene ( Figure 6 ) but none harbored the histidine decarboxylase encoding gene, hdc . Our findings are in line with studies conducted by Inoǧlu and Tuncer (2013) , Ruiz et al (2016) , and Avci and Özden Tuncer (2017) where the authors found that all the analyzed E. faecium strains did not harbor the hdc gene but had the tdc gene. Histamine is the more toxic biogenic amine but the level of tyramine in food must also be controlled.…”
Section: Resultssupporting
confidence: 92%
“…All the five strains showed the expected amplicon of 1100 bp corresponding to the tdc gene ( Figure 6 ) but none harbored the histidine decarboxylase encoding gene, hdc . Our findings are in line with studies conducted by Inoǧlu and Tuncer (2013) , Ruiz et al (2016) , and Avci and Özden Tuncer (2017) where the authors found that all the analyzed E. faecium strains did not harbor the hdc gene but had the tdc gene. Histamine is the more toxic biogenic amine but the level of tyramine in food must also be controlled.…”
Section: Resultssupporting
confidence: 92%
“…E. coli septicemia is normally seen at a much younger age, predominantly under ten days 4 . In older animals, E. coli septicemia, which can be associated with arthritis and osteomyelitis, is seen as an opportunistic infection often in immune compromised animals, 4 and in this case, most probably via infection of the intestinal tract since next to E. coli also E. hirae , a commensal of the gastrointestinal tract, 5 was cultured from an overfilled knee joint in one animal. Feed changes, stress, and diarrhoea could have created the opportunity for invasion of these intestinal tract commensals leading to hematogenous spreading.…”
Section: Discussionmentioning
confidence: 99%
“…Enterococcus faecalis, E. faecium, E. durans, E. hirae, as well as (albeit infrequently) E. saccharominimum and E. italicus, have been isolated from the raw milk of cows, goats, and sheep (Figure 1) [31,36,38,39,41,[45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64]. Additionally, E. dispar, E. malodoratus, E. pseudoavium and E. gallinarum have been isolated both in cow's and in ewe's milk.…”
Section: Raw Milk As a Source Of Enterococci For Dairy Productsmentioning
confidence: 99%